2008
DOI: 10.1063/1.3021459
|View full text |Cite|
|
Sign up to set email alerts
|

Detailed analysis of the microwave-detected photoconductance decay in crystalline silicon

Abstract: An approach to evaluate the microwave-detected photoconductance decay (MWPCD) is developed, which allows to extract the minority carrier lifetime as a function of the excess carrier density from a single MWPCD measurement. The method is shown to be applicable to thin (w≲200 μm) silicon wafers with low minority carrier recombination at the surfaces and bulk lifetimes in the range of about 1–100 μs. Comparison of the MWPCD results with minority carrier lifetime measurements using the quasi-steady-state photocond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…The microwave detected photoconductance decay (µW-PCD) was used to determine the spatially resolved minority charge carrier lifetime [13]. Interface recombination losses were investigated by transient microwave conduction (TRMC) measurements after excitation by an illumination pulse at a wavelength of λ = 1064 nm [14].…”
Section: Interface Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The microwave detected photoconductance decay (µW-PCD) was used to determine the spatially resolved minority charge carrier lifetime [13]. Interface recombination losses were investigated by transient microwave conduction (TRMC) measurements after excitation by an illumination pulse at a wavelength of λ = 1064 nm [14].…”
Section: Interface Characterisationmentioning
confidence: 99%
“…3.3 Passivation of saw damage etched solar cell substrates by a-SiN x :H µW-PCD measurements [13] were utilized to verify the influence of wet-chemical treatments on recombination losses on saw damage etched solar cell substrates [8] under technological conditions. On so prepared a-Si:H/c-Si interfaces also strong correlations were obtained between interface recombination losses and wet-chemical conditioning steps (cf.…”
Section: Photovoltage and Recombination Losses On A-sin X :H/c-si Andmentioning
confidence: 99%
“…A thermal treatment at elevated temperatures can effectively dissociate FeB pairs [6]. Since interstitial Fe and FeB pairs have obviously different recombination activities [2], the association and dissociation of FeB pairs will both lead to a significant variation of carrier lifetime, which can be monitored by the microwave photoconductance decay (MW-PCD) technique [7,8]. It has been reported that the association of FeB pairs needs an activation energy of 0.60 eV [2].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the samples were chemically polished in a mixture of HNO 3 and HF (HNO 3 : HF¼ 3: 1 in volume) for 2 min. The samples were surface-passivated by SiN x :H films grown by a plasma-enhanced chemical vapor deposition (PECVD) technique [7]. After a 200 1C/10 min annealing to eliminate all the FeB pairs, the samples were kept in dark conditions at 50-140 1C to allow the association of FeB pairs until a saturated concentration is reached.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Since Fe i and FeB have different carrier recombination properties, either the dissociation or the association of FeB can be monitored by lifetime measurements. [10][11][12] The association energy E a of FeB has been reported to be in the range of 0.65 to 0.69 eV, while the dissociation energy is in the range of 1.17 to 1.22 eV. 13,14 However, the dissociation energy of FeB can be reduced to 0.09 eV with the help of minority carrier injection, due to a recombination-enhanced defect reaction (REDR) 5 based on the following mechanism [15][16][17] : most of the energy released by multiphonon nonradiative (MPNR) capture or recombination of a carrier can be converted into vibrational energy which is initially localized in the vicinity of the defect.…”
mentioning
confidence: 99%